Conferences: Paris (International Library of African Music, 1983)
The Laboratoire de Langues et Civilisations a Tradition Orale of the Centre National de la Recherche Scientifique, Paris, held a three-day Round Table from the 11th to 13 th October 1982, organised by Simha Arom, on the general theme of “methodologie comparee de la collecte des donnees dans les domaines de l’ethnomusicoiogie et de la tradition orale” (Comparative methodology of data collecting in the fields of ethnomusicology and oral tradition). There were seventeen papers, of which these five referred to Africa.
Keywords: African Music